(untitled) (Research, Society and Development, 2020)
The choice of cultivar to be implanted in a coffee plantation must be based on productivity, quality and grain size, in order to add value to the product. In this context, the objective was to evaluate the productive and quality parameters of coffee cultivars in the Alto Paranaiba region, Minas Gerais. The experiment happened at the Federal University of Uberlandia, Campus Monte Carmelo, in a randomized block design (DBC), with five blocks and eight treatments represented by cultivars of Coffea arabica L. In July 2019, the harvest happened through the use of manual stripping technique on the cloth, being evaluated the following characteristics: productivity (bags benefited of 60 kg ha-1), percentage of green, cane, cherry, raisin and dried fruits, yield (L of “café da roça” to compose a bag of 60 kg of benefited coffee), income (ratio between the weight of the benefited coffee and that of dry coconut coffee, in percentage), sensory analysis according to Specialty Coffee Association of America (SCAA) protocol and classification as to the size and grain shape. The cultivars Acaiá Cerrado MG-1474, Mundo Novo IAC 379-19, Catuaí Vermelho IAC 99 and Topázio MG-1190 stood out due to their higher productivity and income. There was no significant difference between cultivars for yield, obtaining an average of 380.6 L of “café da roça” to compose a 60 kg bag benefited. The highest percentage of cherries, raisins and dried fruits were detected, respectively, in the cultivars Mundo Novo IAC 379-19, Bourbon Amarelo IAC J10 and Acauã Novo (average of 7.78%), Mundo Novo IAC 379-19 and Bourbon Amarelo IAC J10 (average of 21.9%) and Acaiá Cerrado MG-1474, Catuaí Vermelho IAC 99, Topázio MG-1190, IAC 125 RN and Paraíso MG H 419-1 (average of 91.2%). All cultivars have drink scores between 79 and 81 points. The cultivar IAC 125 RN had a higher percentage of high sieve grains, while the cultivars Topázio MG-1190 and Acauã Novo showed a higher amount of small mocha grains.